Penerapan Model Pembelajaran Role Playing Terhadap Peningkatan Keterampilan Berbicara Mata Pelajaran Bahasa Indonesia Pada Siswa Kelas Iv Sdn Pelita Karya Tahun Ajaran 2023/2024 - Wendi Nilpa Apriana; Irna Maharani (KRAKATAU (Indonesian of Multidisciplinary Journals), 2024)
The problem found in this study is the low speaking skills of grade IV students of SDN Pelita Karya. So this study aims to determine how the application of the role playing learning model to improve speaking skills in Indonesian language subjects in grade IV students, and to find out if there is an increase in students' speaking skills with the application of the Role Playing learning model in grade IV. The theoretical basis of the role playing learning model comes from behavioral theory or also called behavioral theory. This research was conducted at SDN Pelita Karya in the 2023/2024 Academic Year. This type of research is Classroom Action Research (CAR), using the CAR design developed by Mc Taggart. The subjects of this study consisted of 36 students. There are two types of data collection techniques in this study, namely observation of teacher activities and student performance tests. Observation is used to obtain data on teacher activities in the process of implementing the role playing learning model while the test is used to collect data on student learning outcomes. The data analysis technique uses mixed methods analysis, because it is carried out in two ways, namely qualitative data analysis and quantitative data analysis. Qualitative data is generated from observations while quantitative data is obtained from the results of the tests given. The results of observations of teacher activities in implementing the role playing learning model in cycle I were 75%, cycle II increased by 100%. The test results showed that the class average was 71.5 in cycle I, then increased in cycle II to an average of 80.6. The percentage of KKTP on the Learning Objective Achievement Criteria was 56% in cycle I, then increased students who met the Learning Objective Achievement Criteria in cycle II by 92%. So from cycle I to cycle II students' speaking skills increased by 36%. Therefore, the application of the Role Playing learning model can improve speaking skills in the Indonesian language subject in grade IV students of SDN Pelita Karya.